Lithium-Ion Battery Waste Management: A Scoping Review Of Recycling Technologies, Environmental Impacts, And Policy Frameworks - Siti Lailatul Rohmah (International Journal of Technology and Education Research, 2026)
The rapid growth of electric vehicles and renewable energy systems has driven unprecedented demand for lithium-ion batteries (LIBs), generating substantial volumes of hazardous end-of-life battery waste with serious environmental and public health implications. This scoping review aims to map the current state of evidence on LIB waste management, encompassing recycling technologies, environmental and health impacts, and governing policy frameworks. A systematic literature search was conducted across Scopus, ScienceDirect, SpringerLink, and Google Scholar, restricted to peer-reviewed articles published between 2020 and 2025. Results indicate that pyrometallurgy, hydrometallurgy, and direct physical recycling each present distinct trade-offs in recovery efficiency, energy demand, and secondary waste generation, with no single approach universally superior. Life cycle assessments demonstrate that environmental outcomes are strongly influenced by energy source, reagent use, and geographic context. Improper LIB disposal poses documented risks including heavy metal leaching, toxic gas release, and fire hazards. Policy frameworks remain inconsistent across jurisdictions, and collection infrastructure is particularly inadequate in developing countries, including Indonesia. This review concludes that sustainable LIB waste management requires an integrated approach combining technological development, comprehensive impact assessment, and robust regulatory governance adapted to local conditions.